Spaceflight Associated Neuro-Ocular Syndrome (SANS): A Systematic Review and Future Directions - Martin Paez, Yosbelkys (Eye Brain, 2020)
PURPOSE: To present a systematic review of the current body of literature surrounding spaceflight associated neuro-ocular syndrome (SANS) and highlight priorities for future research. METHODS: Three major biomedical databases were searched with the following terms: ((neuro ocular) OR ((brain) AND (eye))) AND ((spaceflight) OR (astronaut) OR (microgravity)) AND (ENGLISH[Language]). Once duplicates were removed, 283 papers were left. Articles were excluded if they were not written in English or conference abstracts only. We avoided including review papers which did not provide any new information; however, two reviews on the pathophysiology of SANS were included for completeness. No limitations on date of publication were used. All included entries were then summarized for their contribution to knowledge about SANS. RESULTS: Four main themes among the publications emerged: papers defining the clinical entity of SANS, its pathophysiology, technology used to study SANS, and publications on possible prevention of SANS. The key clinical features of SANS include optic nerve head elevation, hyperopic shifts, globe flattening, choroidal folds, and increased cerebrospinal fluid (CSF) volume in optic nerve sheaths. Two main hypotheses are proposed for the pathophysiology of SANS. The first being elevated intracranial pressure and the second compartmentalization of CSF to the globe. These hypotheses are not mutually exclusive, and our understanding of the pathophysiology of SANS is still evolving. The use of optical coherence tomography (OCT) has greatly furthered our knowledge about SANS, and with the deployment of OCT to the International Space Station, we now have ability to collect intraflight data. No effective prevention for SANS has been found, although fortunately, even with persistent anatomic and physiologic neuro-ocular changes, any functional impact has been correctable with spectacles. CONCLUSION: This is the first systematic review of SANS. Despite the limitations of studying a syndrome that can only occur in a small, discrete population, we present a thorough overview of the literature surrounding SANS and several key areas important for future research are identified.